INFLUENCE OF INDUCED PRESSURE FLUCTUATION ON CRITICAL CAPILLARY NUMBER IN TWO PHASES FLOW IN POROUS MEDIA - ., MD IRFAN (2019)
The purpose of a combination of shear rheometry and core-flooding experimental studies was to understand the oil sweep efficiency after residual oil saturation conditions.